A AVALIAÇÃO DA APRENDIZAGEM NO ENSINO SUPERIOR: práticas avaliativas dos professores do curso de Pedagogia da UESB - Campus de Jequié - Rehem, Cacia Cristina França (2008)
The object of the present study was the evaluation of the learning process in higher education within the Pedagogy course at the Universidade Estadual do Sudoeste da Bahia - UESB Jequié campus. This study aimed to examine the practices developed by professors, from the relationships established with the curriculum. To accomplish that, the theoretical reference that serves as the basis for this thesis is based on studies by Stufflebeam and Shinkifield, Popham, Luckesi, Hoffmann, Vianna, Mendes and others. The research subjects were the professors and students of the selected course. Data were collected through interviews with professors, questionnaires applied to the students and documents on assessment of learning available at MEC, University and the Pedagogy Course. Data analysis revealed that the professor has a concept of formative assessment of learning, which is at the service of the student s learning. However, the data showed that the practices developed are focused on evaluative instruments as tests, seminars and group work and favor the group's performance rather than individual ones as the method of evaluation. They are restricted to an assessment classification perspective, far from the concept presented by the professor. It was observed that the student has a critical view of the evaluative process and realizes that it is assessed only to meet rituals, get grades and, therefore, to be approved or disapproved. Thus, they notice that this evaluation is distant from the elements of the curriculum of the course. We found, analyzing the data, differences between students and professors in relation to the characterization of the current evaluative practices carried out. Despite of the conceptual breakthrough at school s evaluation in recent years, the research has shown the permanence of conservative evaluation practices, restricted to counting the mistakes and the success rate produced by the students. This fact shows that professors have a new speech, but not consistent with the evaluative practices developed in the classroom.